2013
DOI: 10.7243/2052-6954-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in patients with chronic hepatitis B virus infection and naturally immunized individuals

Abstract: Vitamin D deficiency is associated with several adverse health outcomes, and vitamin D appears to have systemic antimicrobial effects that may be crucial in a variety of both acute and chronic illnesses. In the present study, 25-hydroxyvitamin D (25-OHD) levels were compared among patients with chronic hepatitis B virus infection, naturally immunized individuals and control individuals. Thirty-five patients with chronic hepatitis B virus infection (group I), 30 naturally immunized individuals (group II) and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A decrease of 25 OH vitamin D associated with increased iPTH levels have been reported in patients with chronic hepatitis C or B virus infection [16,17,18]. Similarly, in the HCV-infected HD patients, higher iPTH and ALP have been found [1,19].…”
Section: Discussionmentioning
confidence: 90%
“…A decrease of 25 OH vitamin D associated with increased iPTH levels have been reported in patients with chronic hepatitis C or B virus infection [16,17,18]. Similarly, in the HCV-infected HD patients, higher iPTH and ALP have been found [1,19].…”
Section: Discussionmentioning
confidence: 90%
“…In group (I), which represented the inactive HBV disease, the level of vitamin D was significantly higher than group (II), which represented the active HBV infection, suggesting the immunomodulatory effect of vitamin D and its role as anti-microbial agent. [6] This could explain the high viral replication in group (II) compared to group (I) and its subsequent impact on the elevated AST, ALT and AFP levels and relatively reduced levels of albumin in group (II) compared to group (I). The absence of liver cirrhosis and other confounding factors in these groups confirms to a great extent the role of vitamin D in HBV replication and its ability to transform its status from an inactive to an active disease.…”
Section: Discussionmentioning
confidence: 95%
“…Due to its immunomodulatory role, there is growing evidence about the interrelationship between vitamin D and different chronic liver diseases in different stages. [3] Different studies have shown a wide, universal agreement of vitamin D deficiency in patients with chronic hepatitis C virus (HCV) infection, [4,5] chronic HBV, [6,7] nonalcoholic steatohepatitis (NASH) [8] and hepatocellular carcinoma (HCC) [9] with contradictory reports about the impact of vitamin D deficiency on disease pathology and progression.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the role of receptor polymorphism in chronic hepatitis B makes us think that low serum levels of 25(OH)D may have an effect on the course of chronic hepatitis B (14). Thus, in the study by Demir et al (15), 25(OH)D levels were significantly lower in the case group than in the immune and healthy control groups. Similarly, we found that chronic HBV patients had lower levels of 25(OH) D than the control group.…”
Section: Discussionmentioning
confidence: 98%